Análisis del sector industrial y aplicaciones del proceso de fresado y la influencia del efecto Chatter en el acabado de las piezas del proceso (2021)
Chatter is a phenomenon generated by the machining process itself, considered a selfexcited vibration of parts in a machine-tool-workpiece system. Which is widely explained in a range of cutting processes and which has an impact on both the efficiency and the quality of the production process. In recent years, the causes of this phenomenon as well as the theoretical and technological alternatives that provide in a certain way a solution to the aforementioned problems have been a great subject of research, capable of predicting and detecting chatter. The objective of this work is to carry out an analysis of the industrial sectors where it is necessary to apply a monitoring device for CNC milling processes to reduce chatter effects through active control of machining parameters, first of all. media, it was necessary to collect data in search engines recognized for their importance, extracting information that allowed us to see factors of influence within the medium, such as the journal of the article, country of origin of the journal, author, H index and quartile. Where foundations were given for a better understanding of the sectors in which machining processes have a constant contribution to the growth of the industry. As a second phase and having the primary information from the referring documents, key data is extracted from the articles, making a contextualization in an analysis of the application of these mentioned both the variables of incidence of chatter in the milling processes, the sector where these articles they have a field of action and the industrial applications of this. Subsequently, a table of characterization of the variables is made to give complete knowledge of these and how they intervene in the process. Finally, and with the information obtained from said ix documents, an application framework of the monitoring device is elaborated within the current technological capabilities of Colombia and the possible improvements in industrial processes